Lutein-stevioside nanoparticle attenuates H2O2-induced oxidative damage in ARPE cells - Zhuqing Dai; Meimei Nie; Ye Chen; Jiangfeng Song; Yayuan Xu; Zhongyuan Zhang; Guodong Zhang; Shumo Yan; Xing Zhang; Dajing Li (Food Science and Human Wellness)
In order to improve the bioavailability of lutein (LUT), a novel lutein-stevioside nanoparticle (LUT-STE) were prepared previously, but the information about LUT-STE on protecting of eye health was limited. This study investigated the effect of LUT-STE on antioxidant activity of H2O2-induced human retinal pigment epithelial (ARPE) cells. LUT and LUT-STE (final concentration of 5 μg/mL) significantly enhanced cell viability from (74.84 ± 5.10)% to (81.92 ± 10.01)% (LUT) and (89.33 ± 4.34)% (LUT-STE), and inhibited the cell apoptosis (P < 0.05). After pretreatment with LUT-STE in ARPE cells, the levels of superoxide dismutase (SOD), catalase (CAT) and glutathion peroxidase (GSH-Px) in ARPE cells were significantly increased (P < 0.05), the contents of reactive oxygen species (ROS) and malondialdehyde (MDA) were decreased. In addition, the vascular endothelial growth factor (VEGF) levels were inhibited by 13.61% and 17.39%, respectively, pretreatment with LUT and LUT-STE. Western blotting results showed that the pretreatment with LUT-STE inhibited the expression of caspase-9 and caspase-3 and up-regulated Bcl-2/Bax pathway to inhibit H2O2-induced apoptosis. In summary, the novel delivery LUT-STE had more pronounced inhibitory effect on H2O2-induced damage in human ARPE cells.